Structures Understanding (2020)
The structure as composition of an artifact, is the result of a process, analytical, selector and executor research, where the structure is considered from a logical form and function, for example in morphology is sought to correlate the structure to develop fulfilling aesthetic and communicative functions. When we talk about a functional order, the structure must be designed from its three properties that are: stability, rigidity and resistance, which ensures the smooth operation both at rest and subjected to different forces.